2021
DOI: 10.1016/j.ajic.2020.06.214
|View full text |Cite
|
Sign up to set email alerts
|

Exploring stress coping strategies of frontline emergency health workers dealing Covid-19 in Pakistan: A qualitative inquiry

Abstract: Background: The COVID-19 outbreak has gravely impacted the physical and psychological health of people. As the outbreak is ongoing, it is crucial to equip the emergency healthcare workers (HCWs) to be medically and psychologically prepared. Objective: To examine the psychological impact of COVID-19 on emergency HCWs and to understand how they are dealing with COVID-19 pandemic, their stress coping strategies or protective factors, and challenges while dealing with COVID-19 patients. Methods: Using a framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
1
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(182 citation statements)
references
References 55 publications
16
152
1
13
Order By: Relevance
“…The impact of the COVID-19 health and social crisis in Ecuador, during which the present data was collected, seems to be reflected in the professionals’ responses, who reported that almost half of the weekly cases they attended presented a high emotional load. Despite this, the high levels of empathy obtained were in line with those collected from other contexts and methods [ 17 ]. The fact that the professionals who attend to physical health care needs have presented the highest level of personal anguish is consistent with other research [ 18 ] and is understandable since they are the ones in direct contact with death overflowing in the health system.…”
Section: Discussionsupporting
confidence: 79%
“…The impact of the COVID-19 health and social crisis in Ecuador, during which the present data was collected, seems to be reflected in the professionals’ responses, who reported that almost half of the weekly cases they attended presented a high emotional load. Despite this, the high levels of empathy obtained were in line with those collected from other contexts and methods [ 17 ]. The fact that the professionals who attend to physical health care needs have presented the highest level of personal anguish is consistent with other research [ 18 ] and is understandable since they are the ones in direct contact with death overflowing in the health system.…”
Section: Discussionsupporting
confidence: 79%
“…Results of a study on nurses in Pakistan showed that while there were negative emotions during working during pandemic some growth was evident in terms of affection and gratefulness, development of professional responsibility, and self-reflection 15 . The presence of both negative and positive feelings were also found in another study 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this survey provide baseline levels of psychological stress and will allow for the monitoring of interventions designed to support Internal Medicine hospitalists during and after the pandemic in addition to evaluating the effect of pandemicrelated psychological stress on provider burnout and attrition. 4. (If selects MCHS in Q3) What is the primary MCHS site where you practice?…”
Section: Resultsmentioning
confidence: 99%
“…The global spread of SARS-CoV-2 related coronavirus disease 2019 (COVID-19) has caused unprecedented stress to healthcare systems and healthcare workers alike [1]. Data on psychological stress in healthcare workers during the COVID-19 pandemic comes primarily from international sources and has not focused on the hospitalist perspective [2][3][4]. A study among 1,257 healthcare workers in 34 hospitals in China from January 29 through 3 February 2020, identified employee symptoms related to distress (72%), depression (50%), and anxiety (45%) [5].…”
Section: Introductionmentioning
confidence: 99%